Selection, learning, and productivity at the firm level: Evidence from Canadian outward FDI - Hejazi, Walid; Tang, Jianmin; Wang, Weimin (Journal of International Business Studies, 2021)
The superior productivity performance of outward foreign direct investment (FDI) firms is attributable to both ex ante advantages gained within the home market and ex post learning, which emanates from MNE experiences in host markets. Learning is modeled as a function of firm-level R&D efforts, absorptive capacity, and host-country characteristics. Using a firm-level panel database on all firms in Canada, a large-scale econometric analysis is undertaken to show that the host-country environment is central to MNE learning. We also quantify results in the extant literature on the share of the superior productivity exhibited by FDI firms into that which emanates from the home market, and that which is linked to ex post learning, finding 79% attributable to the selection effect, and 21% to the learning effect. The implications of these results are that, since productivity is endogenous to FDI, firms which are below a threshold level required to be successful internationally ex ante can nevertheless succeed if learning can move these MNEs above the required threshold for success ex post. As such, this research provides insights into strategies and host-country environments which lead to ex post productivity improvements for firms undertaking outward FDI, and hence informs the FDI decision at the firm level.